2020
DOI: 10.1108/jhti-06-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Outbound medical tourism experience, satisfaction and loyalty: lesson from a developing country

Abstract: PurposeThe objective of the study is to measure outbound medical tourists' satisfaction and loyalty based on medical tourists' experience from a developing country's perspective.Design/methodology/approachThe medical tourists taken medical services from India constituted the population of this study. By applying a purposive and snowball sampling techniques, samples were selected. Based on the expectation confirmation theory (ECT) and a modified medical tourism experience model, this study empirically analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
1
14
0
2
Order By: Relevance
“…In the past, patients tended to travel from the underdeveloped or developing countries to developed countries but in the last couple of decades, this trend has just reversed (Adams et al, 2015;Aydin and Karamehmet, 2017;Cham et al, 2020;Fetscherin and Stephano, 2016;Khan et al, 2016;Smith et al, 2011;Yu and Ko, 2012;Zarei and Maleki, 2019). Relatively affordable costs with cutting-edge world-class medical services, respite from individual health risk, avoidance of long waiting list, etc., are some of the broad motivating factors for choosing medical tourism which can be linked with the previous research findings ( Bookman and Bookman, 2007;Mahmud et al, 2020;Rodrigues et al, 2017;Sadeh and Garkaz, 2019;Yeoh et al, 2013). Countries like South Africa, Venezuela, Mexico, India, Thailand, Malaysia, South Korea, Singapore, etc., are some of the countries dominating medical tourism market in the last couple of decades (Ormond et al, 2014;Turner, 2010;MacReady, 2007;Burns, 2015;Kirchner et al, 2013;Ehrbeck et al, 2008;Hunter, 2007;Darwazeh, 2011;Dash, 2020).…”
Section: Introductionsupporting
confidence: 66%
“…In the past, patients tended to travel from the underdeveloped or developing countries to developed countries but in the last couple of decades, this trend has just reversed (Adams et al, 2015;Aydin and Karamehmet, 2017;Cham et al, 2020;Fetscherin and Stephano, 2016;Khan et al, 2016;Smith et al, 2011;Yu and Ko, 2012;Zarei and Maleki, 2019). Relatively affordable costs with cutting-edge world-class medical services, respite from individual health risk, avoidance of long waiting list, etc., are some of the broad motivating factors for choosing medical tourism which can be linked with the previous research findings ( Bookman and Bookman, 2007;Mahmud et al, 2020;Rodrigues et al, 2017;Sadeh and Garkaz, 2019;Yeoh et al, 2013). Countries like South Africa, Venezuela, Mexico, India, Thailand, Malaysia, South Korea, Singapore, etc., are some of the countries dominating medical tourism market in the last couple of decades (Ormond et al, 2014;Turner, 2010;MacReady, 2007;Burns, 2015;Kirchner et al, 2013;Ehrbeck et al, 2008;Hunter, 2007;Darwazeh, 2011;Dash, 2020).…”
Section: Introductionsupporting
confidence: 66%
“…As noted by previous researchers [ 70 72 ], a medical tourist’s primary motivation for medical tourism is often driven by the desire to secure high-quality medical care. This seems especially likely for medical tourists departing from Bangladesh, where high costs, unethical practices in the medical supply chain, poor service, improper treatment, long waiting times, and a lack of skilled personnel have been identified as issues within the Bangladeshi health care system [ 46 , 71 , 73 , 74 ]. Based on the previous work of [ 75 ], which found that tourists often use environmental cues to form and guide their perceived image of a destination, the researchers propose that perceived quality of medical care is taking on the role of an environmental cue for Bangladeshi medical tourists, which then shaped their overall formation of DI and significantly impacted all four individual components of destination image.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] and [ 46 ], using a purposive sample of Bangladeshi medical tourists to India, showed that healthcare service quality positively influences medical tourists’ satisfaction, which in turn affects their loyalty, i.e., revisit intention and intention to recommend. However, the satisfaction and loyalty measured in the aforementioned studies were specific to the medical facility, not for the destination as a whole.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on these arguments, our research model is based on these four items to assess tourism factors (see Appendix A). Generally, tourism factors play an important role in the behavioral intention of medical tourists to go abroad [20] and loyalty [29].…”
Section: Tourism Factorsmentioning
confidence: 99%
“…Here, behavioral intention is defined as a patient's willingness to engage in a particular behavior and make plans for an actual medical tour in the future. Most studies on medical tourism support that the predictive nature of behavioral intention can be found in the causal relationship with satisfaction or loyalty [29], service quality [21,24], quality of e-health services [32], perceived value, and overall satisfaction [17,19,24]. Thus, it is used as a dependent variable for this research as well in that we evaluate medical tourists' willingness in terms of the subjective intention level of predisposition, confidence in visiting, and the level of recommendation to others.…”
Section: Behavioral Intentionmentioning
confidence: 99%